Metallographic Investigation on Postweld Heat-Treated0.21%C-1020 Steel Plates Joined by SMAW Method - Saurabh Dewangan; Senthil Kumaran Selvaraj; Karthikeyan B; Tezeta Moges Adane; Somnath Chattopadhyaya; Grzegorz Królczyk; Ramesh Raju (Advances in Materials Science and Engineering)
This paper presents analysis and comparison into mechanical behaviour and microstructural attributes of postweld heat-treated AISI 1020 (0.21%-C) plates joined by the shielded metal arc welding (SMAW) process. The purpose of this work is to heat the welded samples uniformly so that a possible formation of austenite can be obtained, and hence, residual stresses, if any, can be recovered. Four pairs of such steel were taken and welded to form four joints. Welding was followed by heat treatment. The heating temperature and holding time were selected as 1040°C and 60 minutes, respectively. Different cooling media such as sand, water, oil, and air were used to cool the samples. Hence, there were four different samples according to their physical conditions: sand-cooled, water-quenched, oil-quenched, and air-cooled. For analysing mechanical behaviour of all the plates, standard-shaped specimens were prepared out of them. The tensile strength, impact strength, hardness, and the microstructural attributes were analysed in four welded samples after heat treatment. Significant variations in tensile strength and hardness were reported when compared with each other. Oil-cooled sample showed a remarkable enhancement in tensile strength. The sand-cooled sample possessed the highest toughness, whereas water-quenched samples were found to be highly hard. Furthermore, a good combination of strength, hardness, and ductility was reported in oil-cooled sample. Pearlite (coarse and fine) and martensite were the main microstructural findings in the study. A clear vision of ferrite, cementite, and martensite on various heat-treated samples made this study important. All the mechanical properties are in good corroboration with microstructure. A significant refinement into all the mechanical properties was achieved in this work.